Sustainable mobility: a theoretical look and its social reaches - Castro-Garzón, Hernando, Rodríguez Miranda, Juan Pablo, Rivas Trujillo, Edwin (International Journal of Advanced Science and Technology, 2020)
This paper reflects the mobility problems presented by the city of Villavicencio, starting with the thinking of theorists who merely observe individual’s behaviors; they see the world and society in one-dimensional way without considering the relationships between individuals. Subsequently, a deep reflection somewhat philosophical on the social component where the human dimension to the design of cities, and ends in a normative outline in which it is taken into consideration that the power structures have an enormous responsibility for the lack of planning in the distribution of the spaces since Villavicencio responds to a logic of urban development. Thus, the sustainability of mobility is a preponderantly social element, which is in an evident backwardness not only in Villavicencio but also in Latin America.